ASEAN evaluation instruments for Drug Abuse Prevention Education (DAPE) programs. - ASEAN Training Center for Preventive Drug Education ([Quezon City] The Center, 1996)
Manuals for administration (students, teachers, parents) Purpose: This manual aims to develop, validate, and officially adapt proper evaluation instruments for the assessment of drug abuse prevention education programs of ASEAN member countries
"The overall objective of the Project was to develop, validate, and officially adopt appropriate evaluation instruments for assessing drug abuse prevention education programs of the ASEAN member countries. It involves three major stages in developing and validating evaluation instruments suited to the ASEAN situation, cultures, and values, thus, Manuals for Administration for this newly organized set of instruments composed of the Knowledge Test, Attitude Inventory, Checklist, and Open-Ended Questions were developed."
Vol. 1. Manuals for administration -- Vol. 2. ASEAN DAPE evaluation instruments.
Keywords: Drug abuse -- Study and teaching -- Asia, Southeastern -- Handbooks, manuals, etc; Drug abuse -- Prevention -- Asia, Southeastern -- Handbooks, manuals, etc